(untitled) (PerCursos, 2021)
This article some works in the series “Listen to me” by the Portuguese artist Helena Almeida (1934-2018), based on a theoretical reflection that brings together feminism and Marxism. Therefore, the analytical categories of gender (LAURETIS, 1987), ideology (HADJINICOLAOU, 1980), and experience (SPIVAK, 2010) are mobilized in the analysis of the paths taken by the artist during the 60s and 70s. Through her artistic practice, in which the body is a key element, she observes, thinks, registers and criticizes the social and cultural environment to which it was inserted.